Die Primitivrinne der Fluss-Seeschwalbe (Sterna hirundo L.) - Grohs, W. (Leipzig, W. Engelmann, 1906)
Part of this article wiht a plate published in Zeitschr. für Wissensch. Zool. Bd. 85. Heft 3-4. S. 362-390. 1906. Mode of access: Internet.